2012
DOI: 10.1016/j.archoralbio.2012.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Psidium cattleianum leaf extract on enamel demineralisation and dental biofilm composition in situ

Abstract: Psidium cattleianum leaf extract exhibits a potential anticariogenic effect.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
8

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 47 publications
1
30
0
8
Order By: Relevance
“…Alvarenga et al (2013) evaluated the in vivo analgesic and toxicity of a hydroalcoholic extract from P. cattleianum, the results demonstrated that extract demonstrated strong analgesic activity and no toxicity in cultures of LLC-MK2 mammalian fibroblast cells. Aqueous extract of P. cattleianum leaves reduced enamel demineralization, acidogenic potential, microorganism viability, and extracellular polysaccharide production (Brighenti et al, 2012), and a chloroform leaf extract activated specific intracellular death-related pathways, leading to caspase-3 activation and induction of apoptosis in SNU-16 cells (Moona et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Alvarenga et al (2013) evaluated the in vivo analgesic and toxicity of a hydroalcoholic extract from P. cattleianum, the results demonstrated that extract demonstrated strong analgesic activity and no toxicity in cultures of LLC-MK2 mammalian fibroblast cells. Aqueous extract of P. cattleianum leaves reduced enamel demineralization, acidogenic potential, microorganism viability, and extracellular polysaccharide production (Brighenti et al, 2012), and a chloroform leaf extract activated specific intracellular death-related pathways, leading to caspase-3 activation and induction of apoptosis in SNU-16 cells (Moona et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The high concentrations of extracts used in the present investigation in order to inhibit microbial adhesion might be explained by the fact that present investigation used crude extracts in spite of purified preparations 12,13 . Natural products capable of reducing biofilm formation and anti-caries activity seem to act in the synthesis of extracellular polysaccharides 23,[38][39][40] , inhibiting the enzyme glycosyltransferase 39 , or forming a complex directly involved with the adsorption of oral bacteria to the acquired pellicle, delaying the adhesion of the early colonizers of the oral bacterial biofilm 41 . However, initial data have evidenced that phenols, as tannic acid, are deeply involved in both inhibition of cellular metabolism in cariogenic cocci and in the anti-adhesion properties of these extracts 23 .…”
Section: Discussionmentioning
confidence: 99%
“…Natural products capable of reducing biofilm formation and anti-caries activity seem to act in the synthesis of extracellular polysaccharides 23,[38][39][40] , inhibiting the enzyme glycosyltransferase 39 , or forming a complex directly involved with the adsorption of oral bacteria to the acquired pellicle, delaying the adhesion of the early colonizers of the oral bacterial biofilm 41 . However, initial data have evidenced that phenols, as tannic acid, are deeply involved in both inhibition of cellular metabolism in cariogenic cocci and in the anti-adhesion properties of these extracts 23 . Since the extracts are capable to act as denaturants, particularly on proteins such as casein or gelatin, it is possible that these products also interfere in the interactions between microbial adhesins and the receptors on the surface of human cells, acquired pellicle, and early settlers involved in the development of aggregation, although the role of aggregation in cariogenicity of S. mutans remains to be properly studied 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations